Blast performance enhancement prediction of circular column with helical mesh reinforcement and strengthened with UHPFRC plaster, and CFRP wrapping under close-in blast. (5th April 2023) - Tahzeeb, Rafat; Alam, Mehtab; Muddassir, S.M.
A 3-D model of the circular reinforced concrete (RC) column equivalent to the validated square RC column is developed in ABAQUS/ explicit software with 10 mm finite element size and its response is investigated under the axial compression of 950 kN and explosion loading of 82 kg-TNT at scaled distance 1 m/kg 1/3 . To improve the anti-blast resistance of the column, the provision of helical reinforcement mesh with six bars of the area of cross-section equal to the single bar helix, turning each of the six bars successively in the opposite directions has been considered. Performance of the columns is compared. Also, on the columns with helical mesh: 1) 15 mm thick UHPFRC plaster; 2) 2 mm thick wrapping of CFRP, are considered for the blast performance enhancement. Superior blast performance was observed in the case of the column with helical reinforcement mesh strengthened with the CFRP wrapping in terms of damage and maximum displacement.